The direct action of estrone on vascular tissue involves genomic and non-genomic actions - Rauschemberger, María Belén (2008)
A two step model mechanism of steroid action has been recently postulated. In this study, we test the hypothesis that, the biochemical action of estrone (E1) on vascular tissue could be performed via genomic and non-genomic actions. Rat aortic rings or vascular smooth muscle cell cultures (VSMC) were used to test the effect of the hormone on nitric oxide (NO) production, protein kinases activities and cell proliferation. Our data showed that estrone increased NO synthesis between 30 s and 20 min treatment, and this stimulatory effect was dependent on MAPK cascade activation, since it was prevented in the presence of a MAPK inhibitor (PD98059). Using a phosphorylation assay, we also showed that E1 significantly increased MAPK activity. The effect of the hormone on PKC activity was measured in concentrations and time course studies. Direct treatment of rat aortic homogenates with E1 significantly enhanced PKC activity (1-10 fold increase, p < 0.01) at all concentrations (1; 10; 50 nM) and time tested (1-10 min). We demonstrated that 24 h of E1 treatment markedly increased VSMC proliferation (53% above control), and this effect was suppressed by a PKC inhibitor. The rapid and the long term effects of the hormone were completely suppressed in the presence of an estradiol receptor antagonist (ICI 182780). In summary, we provided evidence that, the steroid exerts both non-genomic and genomic actions, the former associated with MAPK kinase dependent on NO production, and the latter related with induction of VSMC proliferation involving PKC pathway activation.